2016
DOI: 10.1124/jpet.115.231381
|View full text |Cite
|
Sign up to set email alerts
|

Combined Treatment with Morphine and  9-Tetrahydrocannabinol in Rhesus Monkeys: Antinociceptive Tolerance and Withdrawal

Abstract: Opioid receptor agonists are effective for treating pain; however, tolerance and dependence can develop with repeated use. Combining opioids with cannabinoids can enhance their analgesic potency, although it is less clear whether combined treatment alters opioid tolerance and dependence. In this study, four monkeys received 3.2 mg/kg morphine alone or in combination with 1 mg/kg D 9 -tetrahydrocannabinol (THC) twice daily; the antinociceptive effects (warm water tail withdrawal) of morphine, the cannabinoid re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 38 publications
0
23
0
Order By: Relevance
“…Unlike m opioid receptor agonists, synthetic k opioid receptor agonists are not likely to be abused because they are devoid of positive reinforcing effects Chavkin, 2011;Tejeda et al, 2013;Lalanne et al, 2014). The antinociceptive effects of k opioid receptor agonists are comparable to those of m opioid receptor agonists in various animal models of pain (Desmeules et al, 1993;Binder et al, 2001;Smith et al, 2008;Kivell and Prisinzano, 2010;Gerak and France, 2016); however, doses producing antinociception also produce conditioned place aversion and diuresis (Leander, 1983;Shippenberg and Herz, 1987;Zhang et al, 2005). Significant adverse effects of k opioids that preclude their use in the clinic include dysphoria, hallucinations, and diuresis (Pfeiffer et al, 1986;Peters et al, 1987;Walsh et al, 2001).…”
Section: Introductionmentioning
confidence: 84%
“…Unlike m opioid receptor agonists, synthetic k opioid receptor agonists are not likely to be abused because they are devoid of positive reinforcing effects Chavkin, 2011;Tejeda et al, 2013;Lalanne et al, 2014). The antinociceptive effects of k opioid receptor agonists are comparable to those of m opioid receptor agonists in various animal models of pain (Desmeules et al, 1993;Binder et al, 2001;Smith et al, 2008;Kivell and Prisinzano, 2010;Gerak and France, 2016); however, doses producing antinociception also produce conditioned place aversion and diuresis (Leander, 1983;Shippenberg and Herz, 1987;Zhang et al, 2005). Significant adverse effects of k opioids that preclude their use in the clinic include dysphoria, hallucinations, and diuresis (Pfeiffer et al, 1986;Peters et al, 1987;Walsh et al, 2001).…”
Section: Introductionmentioning
confidence: 84%
“…However, contrasting findings exist; for example, Nava, Manzato, & Lucchini () did not detect significant correlations between chronic cannabis use and heroin withdrawal or craving in patients receiving methadone maintenance therapy, whereas Wasserman, Weinstein, Havassy, & Hall () revealed the acceleration of heroin relapses during cannabinoid consumption in a similar group otic, rather than natural cannabinoids of methadone‐treated patients. For what concerns SCs, one study revealed that SCs can increase mu‐opioids signaling and potentiate opioid antinociceptive effects (Gerak & France, ), which can contribute to explain our study finding of individuals using SCs as an alternative to opioids. The cross‐tolerance of SCs and opioids can lead to coaddictive effects for both classes of substances (Gerak et al, ).…”
Section: Discussionmentioning
confidence: 62%
“…According to animal studies, the agonistic influence of cannabinoids supports the growth of antinociceptive tolerance as well as it attenuates and modulates morphine withdrawal syndrome (Gerak, Zanettini, Koek, & France, 2015). (Gerak & France, 2016), which can contribute to explain our study finding of individuals using SCs as an alternative to opioids. The cross-tolerance of SCs and opioids can lead to coaddictive effects for both classes of substances (Gerak et al, 2015).…”
Section: Discussionmentioning
confidence: 72%
“…The endocannabinoid (eCB) system is a promising target to mitigate pain as an alternative to the opioid system. There is also evidence that there is a synergism between the eCB and the opioid system that reduces the need for high doses of opioids 8 . Hence, it is important to understand the function of eCBs and their metabolites as endogenous and exogenous ligands of the receptors that are involved in pain response modulation.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, cannabis has been used for centuries to reduce nociceptive pain either alone or in combination with opioids 8 . The primary components of cannabis interact in the body with cannabinoid receptors 1 and 2 (CB1 and CB2) and other GPCRs [9][10][11] .…”
Section: Introductionmentioning
confidence: 99%